Practical SCADA for industry - Bailey, David; Wright, Edwin (Amsterdam ; London : Elsevier, 2003)
A SCADA system gathers information, such as where a leak on a pipeline has occurred, transfers the information back to a central site, alerting the home station that the leak has occurred, carrying out necessary analysis and control, such as determining if the leak is critical, and displaying the information in a logical and organized fashion. SCADA systems can be relatively simple, such as one that monitors environmental conditions of a small office building, or incredibly complex, such as a system that monitors all the activity in a nuclear power plant or the activity of a municipal water system. An engineer's introduction to Supervisory Control and Data Acquisition (SCADA) systems and their application in monitoring and controlling equipment and industrial plant Essential reading for data acquisition and control professionals in plant engineering, manufacturing, telecommunications, water and waste control, energy, oil and gas refining and transportation Provides the knowledge to analyse, specify and debug SCADA systems, covering the fundamentals of hardware, software and the communications systems that connect SCADA operator stations.
Background to SCADA; SCADA Systems Hardware (and Firmware); SCADA Systems Software and Protocols; Landlines; Local Area Network Systems; Modems; Central Site Computer Facilities; Troubleshooting and Maintenance; Specification of Systems; Appendix A: Glossary of Terms; Appendix B: Interface Standards; Appendix C: CITECT Practical.
Keywords: Automatic data collection systems; Supervisory control systems; Electronic books